Atmospheric radioactive nuclide deposition on the coast of the Maowei Sea, northern Beibu Gulf, China - Wang, Xilong; Zhou, Jiaodi; Su, Kaijun; Du, Jinzhou; Wei, Longtao; Li, Xing; Du, Juan; Lu, Dongliang (Frontiers in Marine Science, 2023)
The natural radioisotopes (7Be, 210Pb and 210Po), with different half-lives, are all particle-reactive and served as natural tracers to study sources and transportation of sediments, sedimentation rates, sediment chronology, etc. Atmospheric deposition of these radioisotopes are the the premise and foundation of their tracing application. Maowei Sea is a semi-closed bay along the Beibu Gulf which is an important gulf in the northwest of the South China Sea, but the atmospheric deposition of the above radioisotopes has not been systematically reported along the coast. In this paper, the atmospheric depositional fluxes of 7Be, 210Pb and 210Po were observed over a period from June 2018 to December 2021 at the coast of Maowei Sea. The annual atmospheric depositional fluxes (Bq m-2 yr-1) of 7Be, 210Pb and 210Po at the coast of Maowei Sea were 496.80, 201.72, and 58.08, respectively. Both of the distributions for 7Be and 210Pb depositional fluxes during a whole year (the year of 2019 and 2021) followed a bimodal pattern, with one peak from February to April and another peak from August to October, while the distribution for 210Po depositional flux showed only one peak during the year of 2019 and 2021. The deposition flux and activity of 7Be showed a strong positive correlation with the deposition flux and activity of 210Pb, respectively; the deposition flux and activity of 210Po also showed positive correlations with the deposition fluxes and activities of 210Pb and 7Be, respectively, indicating a similarly scavenging behavior from the atmosphere. A Pearson correlation matrix was used to illustrate the factors influencing the atmospheric depositions, and found that precipitation, air quality index (AQI), and PM (both PM2.5 and PM10) were the major factors that may influence the deposition of these three radionuclides. Precipitation had significant positive correlations with all three radionucildes’ deposition fluxes, indicating that rainfall was the main scavenging way from the atmosphere for these radionuclides. The observations for the specific single rainfall events and their air mass backward trajectory analysis showed that the air masses movement during the rainfall may be another important factor that impacted the depositional fluxes for 7Be, 210Pb and 210Po.